Exploratory Data Analysis with MATLAB, 3rd ed., by Wendy L. Martinez, Angel R. Martinez, and Jeffrey L. Solka: 3rd ed.,by Wendy L. Martinez, Angel R. Martinez, and Jeffrey L. Solka. Boca Raton, FL: Chapman & Hall/CRC Press, 2017, xxv + 590 pp., $140.00(H), ISBN: 978-1-49-877606-6 - Ni, Yang (American Statistician, 2022)
It provides brief background of EDA, overview of the covered topics, description of four datasets used throughout the book, and several data transformation techniques. Exploratory data analysis (EDA), "numerical detective work" according to John W. Tukey, is a field in statistics, which explores, analyzes, and visualizes data without pre-specified hypotheses. Chapters 8-10 introduce various methods for visualizing clusters, univariate and multivariate densities, dependencies, summary statistics, and dimension reduction, with the primary focus on continuous data.